Estudo do imposex em muricídeos do gênero Stramonita (Mollusca: Gastropoda) no Nordeste do Brasil - Castro, Italo Braga de (2005)
Imposex consists of a superimposition of male sexual characteristics in female prosobranch molluscs exposed to organotin compounds (OCs) contamination. This contamination is caused by biocides present in antifouling paints used on boats all over the world. Since imposex leads to measurable characters, those have been used for biological-effect monitoring of this type of contamination. This present work had the objective to monitor the organotin contamination along the areas under influence of the 10 most important harbours in the northeastern coast of Brazil, and also to compare the imposex development in the muricid species studied. Those species were Stramonita haemastoma and Stramonita rustica. The indices used to quantify the imposex development were VDSI, RPSI, RPLI and the imposex percentage. In all harbour areas, there was at least one site where imposex was detected, what strongly sug gests the presence of OCs contamination. However, the indices observed appeared to be lower when compared to the indices of other monitorings in industrialized regions, such as Europe and Asia. When compared tostudies in Guanabara Bay – Rio de Janeiro,Brazil,the indices also seemed ver low. This einforces the data already mentioned in other studies, which suggests that the higher the level of industrialization in an area more severe is the contamination by organotin compounds. Comparative studies of imposex development in the species Stramonita haemastoma and S. rustica revealed that the former is more sensitive to OCs contamination, once that, when submitted experimentally to equal concentrations and same exposure time, S. haemastoma presented a much greater response than S. rustica. In this present study, 82 sites were analyzed, 32 appeared to be free from any imposex evidence, what suggests that imposex does not appear as a natural characteristic in those S. haemastoma and S. rustica.